2022
DOI: 10.3389/fpubh.2022.870157
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Health Changes and Community Health Screening Participation Among Older People

Abstract: The utilization of health screening and other community health services has been a hot topic in China. Thus, this study examined the effect of health changes (self-rated health, physical health, and mental health) on older people's community health screening participation in China. We derived the data from the 2016 and 2018 waves of the Chinese Longitudinal Aging Social Survey (CLASS). This paper included 10,992 observations in two waves. We tested the causal relationship using the fixed effects model. Approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…There have been inconsistent reports regarding the direction of the association between educational level and participation in medical check-ups. In contrast to our findings, Benfeng et al reported that since highly educated elderly individuals were concerned about their health, they sought high-quality medical check-ups rather than complimentary periodic medical check-ups, which resulted in a low participation rate [ 27 ]. Contrastingly, we observed a positive correlation between education level and participation in medical check-ups, which could be attributed to a lack of awareness about health care or ignorance of the presence of medical check-ups.…”
Section: Discussioncontrasting
confidence: 99%
“…There have been inconsistent reports regarding the direction of the association between educational level and participation in medical check-ups. In contrast to our findings, Benfeng et al reported that since highly educated elderly individuals were concerned about their health, they sought high-quality medical check-ups rather than complimentary periodic medical check-ups, which resulted in a low participation rate [ 27 ]. Contrastingly, we observed a positive correlation between education level and participation in medical check-ups, which could be attributed to a lack of awareness about health care or ignorance of the presence of medical check-ups.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Andersen’s healthcare utilization model, healthcare utilization is influenced by four elements: environmental, demographic characteristics, health behavior, and health outcomes 22 . From a psychological perspective, social isolation in old age is considered a potential obstacle to participation in health programs 21 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Older adults experiencing geriatric depression are less likely to adopt health-promoting behaviors compared with those not experiencing it 20 . Furthermore, the post-retirement experience of anxiety contributes to this mentally vulnerable state, hindering the utilization of health check-ups among older adults 21 , 22 . On the other hand, social support serves as motivating factors for older adults to engage in healthy behaviors 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar pattern is seen in research that shows a significant association between health screening participation and increasing age. 26,[28][29][30] Higher satisfaction with their health among younger CHVs in BHP MYS may also have contributed to the lower number and frequency of self-reported lifestyle changes.…”
Section: Discussionmentioning
confidence: 99%